The Role of Triglyceride/Glucose Index in patients with Polycystic Ovary Syndrome - Atlihan, Ufuk; Erkilinc, Selcuk; Ersak, Burak; Acet, Ferruh; Ozay, Ali Cenk; Yavuz, Onur; Avsar, Huseyin Aytug; Ata, Can; Bildaci, Tevfik Berk (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: Our study aimed to examine the function of triglyceride/glucose (TyG) index, TyG-BMI, HOMA-IR, and conventional lipid ratios in determining IR in women with PCOS and to evaluate whether the TyG index is a clinical marker for IR. STUDY DESIGN: A total of 171 individuals with PCOS and 93 control patients who were admitted to our gynecology clinic between January 2018 and January 2024 were evaluated retrospectively. BMI, FBG, QUICKI, HOMA-β, HOMA-IR, FSH, LH, TyG-BMI, TyG, LDL-C, HDL-C, TG, TC, and fasting insulin levels of all patients were retrieved from the hospital database and evaluated retrospectively. RESULTS: The TyG index was significantly higher (8.35±0.44) in the PCOS group compared to the control group (8.23±0.36) (p=0.04). The PCOS group had a significantly higher TyG-BMI index (217.93±46.2) than the control group (199.16±42.4) (p=0.026). The PCOS group had a substantially higher TC/HDL-C ratio (4.52±1.36) than the control group (3.94±1.62) (p=0.016). The PCOS group had a significantly higher TG/HDL-C ratio (2.75±1.18) than the control group (2.15±1.12) (p=0.008). CONCLUSION: According to our research, the TyG index and TyG-BMI demonstrated a strong predictive power in identifying impaired insulin sensitivity in female PCOS patients. The TyG index can serve as a potential surrogate marker for calculating IR in female PCOS patients, as TG and glucose tests are both commonly performed and cost-effective. Further large-scale prospective and epidemiological studies are needed to validate these findings.